Предмет: Алгебра,
автор: лайф
решите уравнение y'= 0, если у = 3х2 - 2х3 + 6
Ответы
Автор ответа:
0
Сначала вычислим производную:
y' = (3х² - 2х³+ 6)' = (3х²)' - ( 2х³)' + (6)' = 3*2х - 2*3х² + 0 = 6х - 6х²
Решаем уравнение y'= 0
6х - 6х² = 0
6х(1 - х) = 0
х = 0 или 1 - х = 0
х = 1
Ответ: 0 ; 1.
Похожие вопросы
Предмет: Математика,
автор: fakeaccoun24
Предмет: Русский язык,
автор: pavelkrapivin445
Предмет: Українська мова,
автор: gosancernenko
Предмет: Математика,
автор: неуч1
Предмет: Геометрия,
автор: буквы3